Impact of Treatment with Imatinib on Renal Histology in Albino Rats - Al-Allaf, Luma; Al-Ashoo, Hafidh (Jordan Medical Journal, 2020)
Background: Targeted small molecule drugs have revolutionized treatment of chronic myelogenousleukemia(CML) over the last decade. however, their use has been found to be associated with serious toxiceffects on a number of vital organs including the kidneys.Objectives: This study aims to determine the histological changes of the kidney of rats after administrationof a dose of 75mg/kg/once/day of Imatinib mesylate for one month in comparison to control ones.Study setting and design: This experimental study was conducted on 16 male Albino rats purchased fromAnimal Houses of Veterinary College, University of Mosul, Mosul, Northern Iraq.Methods: In this study a group of eight rats (40- 45 days) were administered orally daily dose of 75mg/Kg/30days of imatinib mesylate (Glivec®; Novartis). Another group of 8 rats (40- 45 days) were administereddistilled water(D.W) . Kidneys tissues from each rat were obtained. The tissues were embedded in paraffinand stained with hematoxylin-eosin, periodic acid schiff +Hematoxylin stain, Toluidin blue, and Masson’sTrichrome.Results: Rats treated with 75mg/kg /once/day of imatinib for 30 days showed different histological changesin glomeruli and some parts of the urinary tubules in comparison with controls. The most evident featuresare increase in Bowman's space, presence of lobulated or segmented glomeruli, shrunken glomeruli, dilatedtubules with sloughed epithelium, and cloudy degeneration. Congested glomerular capillaries are alsonoticed sometimes in these sections with decreased Bowman's space .Dramatic renal injury in these rats wasrepresented with tubular cell swelling, loss of brush border of proximal convoluted tubules as well aspresence of cloudy degeneration of tubules. In addition, there was a focal accumulation of inflammatorycells of early inflammation that infiltrate between the tubules at the cortical and corticomedullary portionand early fibrosis is noticed. Sections obtained from rats treated with imatinib exhibit dilatation andhyperemia in the intertubular cortical or juxtamedullary blood vessels with appearance of structurelessesinophilic area of necrosis . In addition , dilated tubules with accumulation of eosinophilic homogenousmaterial in tubular lumen were noticed . The interstitial tissue showed area of hypercellularity, interstitialoedema and infiltration of mononuclear inflammatory cells (lymphocytes) which tend to be concentratedaround the tubules in the cortical and medullary zones.Conclusion: Imatinib has adverse effects on the renal histology and results in alterations in the renal cortexglomerular cells or tubular, which could play an important role in renal dysfunction. A clinical collaborationbetween oncologists and nephrologists could be useful with the objective to optimize the management oftyrosine kinase inhibitors.